Pengaruh Model Pembelajaran Problem Posing Tipe Within-Solution Posing Terhadap Kemampuan Pemecahan Masalah Matematika Siswa - Fahruzain, M Ilham; Abdullah, Ahmad Anis (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2024)
The problem in this research is the low ability of students to solve mathematical problems because students are less accustomed to solving problem-based questions and also the learning model used is less effective in improving mathematical problem solving abilities. This research aims to see the influence of the Problem Posing learning model of Within Solution Posing type on the mathematical problem solving abilities of class VIII students in cube and block material. This type of research is quasi-experimental research with a non-equivalent control group design. The population in this study were all class VIII students at MTs Nurul Ummah Kotagede Yogyakarta, totaling 73 homogeneous students. The sampling technique in this research was simple random sampling, class VIII C and class VIII D were selected as samples for this research. With the number of students in class VIII C totaling 19 students and class VIII D totaling 18 students. The research instrument used was essay questions to test students' mathematical problem solving abilities using cube and block material in the form of a pretest and posttest. The results obtained show that there is a significant influence on students' mathematical problem solving abilities after being given treatment using the Within Solution Type Problem Posing learning model.